2018
DOI: 10.1111/bcp.13525
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione‐PEGylated liposomal methylprednisolone in comparison to free methylprednisolone: slow release characteristics and prolonged lymphocyte depression in a first‐in‐human study

Abstract: 2B3-201 is considered safe, with no clinically relevant changes in central nervous system safety parameters and no serious adverse events. In addition, 2B3-201 shows a long plasma half-life and prolonged immunosuppressive effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…• slow release formulation with reduced toxicity and prolonged decrease in the lymphocyte count [171] PLGA Pitavastatine Healthy volunteers 40 patients, Phase I, iv administration…”
Section: Discussionmentioning
confidence: 99%
“…• slow release formulation with reduced toxicity and prolonged decrease in the lymphocyte count [171] PLGA Pitavastatine Healthy volunteers 40 patients, Phase I, iv administration…”
Section: Discussionmentioning
confidence: 99%
“…As an example, the major results obtained with 2B3-101 in cells and animals are presented in Figure 5 . The 2B3-201 product has recently completed a phase I trial in healthy volunteers [ 146 ], while the 2B3-101 product has completed a phase I/IIa trial in patients with various forms of brain cancer ( Identifier: NCT01386580 [ 147 , 148 ]) and is currently being tested in a phase II trial in patients with breast cancer and leptomeningeal metastases (ClinicalTrials.gov Identifier: NCT01818713).…”
Section: Gsh Decoration As a Tool For Targeted Drug Delivery Systementioning
confidence: 99%
“…It is hard to evaluate to what extent the pre-medication administered to the patient played a role in avoiding IRs, but from an ethical point of view pre-treatment was mandatory to reduce the potentially life-threatening side effects of IRs. In addition, with other nano-drugs, it is known that despite pre-medication some patients still experience IRs to several types of drugs such as antibodies [60] but also anticancer therapy [34], or lately a new formulation of glutathione-PEGylated liposomal methylprednisolone [50]. Therefore, pre-medication was, and should still be administered, as a mean of prevention even though our formulation didn't give any signs of complement activation in the patient.…”
Section: Discussionmentioning
confidence: 98%
“…They measured the levels of SC5b-9 as an indication of complement activation in the plasma of patients treated with Doxil ® , and showed that the correlation between complement activation and infusion reaction was the strongest when the levels of SC5b-9 were raised 4-fold or more above the upper threshold of normal plasma levels. A recent clinical study with a formulation of glutathione-PEGylated liposomes containing methylprednisolone [50] revealed an extremely high rate of infusion related reactions (89%) in patients following drug infusion. Analysis of complement activation factors in the blood of patients revealed drastic increase in C3a factor (spiking at>1500 ng/mL) and an increase in Bb levels of more than 16-fold in all patients receiving doses of 300 mg or more of liposomal MPS.…”
Section: Discussionmentioning
confidence: 99%